Development and Implementation of LPG/Gasoline Bi-Fuel Engine Teaching Media for Vocational High Schools - Muji Setiyo; Saifudin Saifudin; Agus Setiawan; Muhammad Latifur Rochman; Sofyan Kurniawan; Dhasa Ikrar Setyanansyach (Universitas Muhammadiyah Magelang, 2023)
In 2022, the World Liquified Petroleum Gas Association (WLPGA) reported that there are more than 28.3 million LPG-fueled vehicles used throughout the world with an increasing trend in the last 20 years. The growth of LPG-fueled vehicles will require more mechanics from vocational school graduates who master environmentally friendly technology. Considering the availability of resources, Muhammadiyah Vocational High School 1 Bandongan Magelang (SMK MUTU Bandongan) has the potential to complement the competencies of graduates with mastery and skills in servicing modern and environmentally friendly vehicles, as one of their uniqueness from others. Therefore, we develop and implement environmentally friendly automotive technology learning media, especially LPG-fueled vehicles at SMK MUTU Bandongan. This is an implementation of research on LPG-fueled vehicles over the last 10 years. Activities are carried out through (1) rebuilding and reconditioning the engine which will be modified into a bi-fuel engine; (2) procurement and installation of converter kits; and (3) increasing teacher competency.